Impact of the establishment of Loviisa - Kunda ferry connection in activating the Eastern Finland - Estonia transport corridor - Reima Helminen; Riitta Pöntynen; Minna Alhosalo; Aado Keskipaik; Rivo Noorkõiv (Turun yliopiston Brahea-keskus / Brahea Centre at the University of Turku, 2022)
The launching of the ferry connection between the port of Loviisa in Finland and port of Kunda in Estonia would operationalize the transport corridor between Eastern Finland and Eastern Estonia (REFEC corridor). The aim of the study is to analyse the impacts generated by the foreseen ferry line. The impacts consist of comparisons of the Loviisa-Kunda route with the current existing port connections between Finland and Estonia. They encompass difference in the mileage, travel time, costs, CO2 emissions and impact to regional development. The study results are based on measurements, statistical analysis, planning documents and interviews of stakeholders of different interest groups linked to regional development. The comparison of mileages from REFEC area towns between Finland and Estonia expectedly shows that Loviisa-Kunda ferry would provide shorter mileage compared to the routes via the existing ferry services. The aggregate distance between REFEC area major towns in eastern Finland and Estonia via Loviisa-Kunda is 30%-85% shorter compared to the other connections. As for travel time, including ferry travel, the relative advantage of Loviisa-Kunda route narrows but it is faster than other alternatives. The very southeastern Finland cargoes would get the best advantage of the foreseen new ferry connection. As for the costs, the new ferry line would provide about ¼ lower costs for the estimated freight potential between eastern Finland and northeastern Estonia. Majority of Finnish truck transports crossing the Gulf of Finland transit Estonia on their way to Central Europe. For Finnish REFEC area cargoes to/from Central Europe, the routing via Loviisa- Kunda would not in general be much more time consuming or costly compared to the alternative ports. For some origins/destinations like Kouvola, Lappeenranta and Joensuu the Loviisa-Kunda ferry would provide the lowest cost. Although Loviisa-Kunda ferry would seem a competitive alternative for the transports between eastern Finland and northeastern Estonia, as well as for Central Europe and beyond, there are many components which affect the eventual costs in real life, and which could not be incorporated into the study. These are e.g. the cost of ferry ticket, the cost structure of the transport company (age of fleet etc), the actual ferry schedules (calculations used averages), how driver’s previous driving time and ferry schedule match with the driving and rest time regulation, thus affecting the aggregate travel time etc. The CO2 emissions are very much in line with the distance of origins and destinations. The emissions consist of road and sea components where the longer sea voyage between Loviisa- Kunda is compensated by shorter mileage to these two ports. Transports in eastern area of REFEC corridor via Loviisa-Kunda have less CO2 emissions compared to the other port alternatives. Transports from Finnish REFEC area towns to Pärnu emit more CO2 thanvia Vuosaari-Muuga or West Harbour-Old City but less than via Hanko-Paldiski. One of the major benefits of Loviisa-Kunda ferry line would be relieving the congestion in the capital cities. The activation of the Loviisa-Kunda ferry service would re-route around 6-12% of the Helsinki-Tallinn ferry related truck traffic away from the centres of Helsinki and Tallinn. Negative impacts of the relocated traffic are not expected. The Finnish transport strategies or maritime spatial plans include no indication of the foreseen new ferry connection while the Estonian strategy documents (spatial and maritime spatial plans) on national, regional and local level have been explicitly included port of Kunda having a ferry connection to Finland. A new ferry line would stimulate regional development close to the ports in both countries. It is estimated to generate new jobs (Finland 25-37 jobs and Estonia 25-50 jobs), tax income to municipalities (FI 170-250 k€; EE 40-80 k€) and two million euros annual turnover to both ports. Major beneficiaries would be the manufacturing and logistics industries. Moreover, it would add the vitality of the ports and lead to cluster type development with growing mutual benefits. A ferry connection would bring new investments to both regions. The improved accessibility of eastern Uusimaa and western Virumaa would lead to improved Finnish-Estonian economic cooperation of the stakeholders and increased commuting and leisure time.